2018
DOI: 10.1002/cae.21950
|View full text |Cite
|
Sign up to set email alerts
|

Feedback by automatic assessment systems used in mathematics homework in the engineering field

Abstract: This research presents the results of the teaching innovation Dynamic Online Assessment System in Mathematics, which is implemented in higher education to promote self‐study by students outside the classroom. The WIRIS calculator was integrated into the Moodle platform to create questions with random elements, for example, students had access to different variants of the same question. The effect of the type of feedback (immediate or deferred) on the work of the students on the platform, measured by means of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 16 publications
(21 reference statements)
0
7
0
11
Order By: Relevance
“…This is an approach to motivate people and change their personalities through discovering new thoughts, mastering new skills and satisfying their requirements Chemsi et al, ( 2020 ) Computer adaptive testing (CAT) The CAT tries to modify the selection of questions to maximize the information obtained. It can be proved that this condition is equivalent to the selection of the question whose difficulty is closer to the currently estimated student knowledge Conejo et al, ( 2016 ) Quasi‐experimental research methodology Quasi-experimental research methodology has two equivalent groups and no control group in which successive measures have been conducted but always within the intervention, that is, under the influence of the independent variable Gaona, et al, ( 2018 ) The DeLone & McLean IS success model This model was first introduced in 1992, in which the system quality, information quality, use, user satisfaction, individual impact, and organizational impact are distinct, but related dimensions of IS (Information systems) success Marjanovic et al, ( 2016 ) Activity theory Activity theory has been an interdisciplinary approach to human science and an evolving theoretical framework through several generations and multiple perspectives Park & Jo, ( 2017 ) Merrill's problem-centric framework This framework is to engage with students cognitively, emotionally, and behaviourally. This framework was proposed in 2013, designing principles for “e3 learning” (effective, efficient, and engaging learning) Wang, ( 2019 ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an approach to motivate people and change their personalities through discovering new thoughts, mastering new skills and satisfying their requirements Chemsi et al, ( 2020 ) Computer adaptive testing (CAT) The CAT tries to modify the selection of questions to maximize the information obtained. It can be proved that this condition is equivalent to the selection of the question whose difficulty is closer to the currently estimated student knowledge Conejo et al, ( 2016 ) Quasi‐experimental research methodology Quasi-experimental research methodology has two equivalent groups and no control group in which successive measures have been conducted but always within the intervention, that is, under the influence of the independent variable Gaona, et al, ( 2018 ) The DeLone & McLean IS success model This model was first introduced in 1992, in which the system quality, information quality, use, user satisfaction, individual impact, and organizational impact are distinct, but related dimensions of IS (Information systems) success Marjanovic et al, ( 2016 ) Activity theory Activity theory has been an interdisciplinary approach to human science and an evolving theoretical framework through several generations and multiple perspectives Park & Jo, ( 2017 ) Merrill's problem-centric framework This framework is to engage with students cognitively, emotionally, and behaviourally. This framework was proposed in 2013, designing principles for “e3 learning” (effective, efficient, and engaging learning) Wang, ( 2019 ) …”
Section: Resultsmentioning
confidence: 99%
“…A further study investigated automatic detection of learning styles by analysing student learning behaviour by constructing a mathematical model (Xiao & Rahman, 2017 ). Further research has been suggested in the areas of exploring the extent to which automatic feedback encourages positive motivational beliefs and self‐esteem among students (Gaona, et al, 2018 ), improving real-time adaptation learning modules, intelligent non-human tutoring, and using educational data mining techniques to investigate and predict students' attitude to learning.…”
Section: Resultsmentioning
confidence: 99%
“…Esto habla de la penetración de este tipo de tecnología. Particularmente en Latinoamérica se reportan usos en Chile (Gaona, Reguant, Valdivia, Vásquez, & Sancho-Vinuesa, 2018b), Colombia (Ocaña et al, 2019) y México (Pacheco-Venegas et al, 2015). Todos en educación superior.…”
Section: Resultsunclassified
“…El otro trabajo reportado es en educación superior en un curso de nivelación y se usa Moodle/Wiris-Quizzes (Gaona et al, 2018a). Se analiza la diferencia en el trabajo de los estudiantes al variar el momento en que se suministra la retroalimentación paso a paso: inmediatamente o diferida (una vez terminado el cuestionario).…”
Section: Impacto En El Trabajo De Los Estudiantesunclassified
“…On that basis, the traditional-lecture approach may not provide students with properly timed opportunities to practice, the teaching and practice it does provide may be missing essential components and the feedback it provides may not be properly timed or targeted [16][17][18][19][20][21][22][23][24][25][26][27][28]. The homework in the traditional-lecture approach is used for assessment; there are no opportunities for students to practice and receive feedback on their solution prior to being assessed.…”
Section: Research Hypothesesmentioning
confidence: 99%